Assessing wastewater heat resources in Zambian food and beverage processing: Case studies, regional assessment, and implications - Eleanor Mancusi-Ungaro; Madhu K. Murali; Paul Coughlan; Godfrey Hampwaye; Derrick Bwalya Tembo; Aonghus McNabola (Energy Conversion and Management: X)
Wastewater heat recovery (WWHR) aims to recycle low-grade thermal resources embedded in wastewater discharges and lower the energy requirements for hot-water production in various settings. WWHR has received growing attention in recent years, however, limited attention has been given to potential WWHR resources or the technologies required to exploit these in hot-water-intensive industrial settings, such as food and beverage processing. In addition, very limited attention has been given to WWHR in a Global South context. To address these gaps, and an additional gap on WWHR in subtropical locations, this paper seeks to quantify the thermal resources available in Zambia’s food and beverage industry. Two potential WWHR resources were selected for deeper analysis based on site assessments: boiler blowdowns and cleaning-in-place. This analysis shows a significant heat resource in both processes based on analysis of on-site data and nationwide extrapolation. Cleaning-in place processes also represent a new avenue for WWHR currently not explored in the literature. Extrapolating the WWHR findings to a country-wide scale showed that boiler blowdowns have an annual thermal potential of about 4 GWh and cleaning-in-place had an annual thermal potential of 4.4 GWh. In summary, this paper demonstrates that the Zambian food and beverage processing sector has a significant wastewater heat resource. Recovering this heat could reduce sector emissions by around 2.5 kT CO2 equivalent emissions per year. These results also demonstrate the potential of industrial WWHR in subtropical climates and the potential for this source of renewable heat warrants exploration regionally beyond the national context of Zambia.